Diaphragm dysfunction after severe COVID-19: An ultrasound study - Boussuges, Alain; Habert, Paul; Chaumet, Guillaume; Rouibah, Rawah; Delorme, Lea; Menard, Amelie; Million, Matthieu; Bartoli, Axel; Guedj, Eric; Gouitaa, Marion; Zieleskiewicz, Laurent; Finance, Julie; et al. (Frontiers in Medicine, 2022)
Background: SARS-CoV-2 infection can impair diaphragm function at the acute phase but the frequency of diaphragm dysfunction after recovery from COVID-19 remains unknown. Methods: This study was carried out on patients reporting persistent respiratory symptoms three to four months after severe COVID-19 pneumonia. The included patients were selected from a medical consultation designed to screen for recovery after acute infection. Respiratory function was assessed by a pulmonary function test, and diaphragm function was studied by ultrasonography. Results: 132 patients (85M, 47W) were recruited from the medical consultation. During the acute phase of the infection, the severity of the clinical status led to ICU admission for 58 patients (44%). Diaphragm dysfunction (DD) was detected by ultrasonography in 13 patients, two of whom suffered from hemidiaphragm paralysis. Patients with DD had more frequently muscle pain complaints and had a higher frequency of prior cardiothoracic or upper abdominal surgery than patients with normal diaphragm function. Pulmonary function testing revealed a significant decrease in lung volumes and DLCO and the dyspnea scores (mMRC and Borg10 scores) were significantly increased in patients with DD. Improvement in respiratory function was recorded in seven out of nine patients assessed six months after the first ultrasound examination. Conclusion: Assessment of diaphragm function by ultrasonography after severe COVID-19 pneumonia revealed signs of dysfunction in 10% of our population. In some cases, ultrasound examination probably discovered an un-recognized pre-existing DD. COVID-19 nonetheless contributed to impairment of diaphragm function. Prolonged respiratory physiotherapy led to improvement in respiratory function in most patients.